2015
DOI: 10.12779/dnd.2015.14.4.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Illiteracy on Cognition and Cerebral Morphology in Later Life

Abstract: Background and Purpose A better developmental environment has positive effects on brain development. The acquisition of literacy during childhood may affect brain functional organization. The present study aimed to evaluate the effects of illiteracy on neuropsychological test results and cerebral morphology in later life. Methods We recruited 7 illiterate elderly farmers who had never attended school and had no reading or writing knowledge. These subjects were compared with 9 literate subjects in terms of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
1
0
1
Order By: Relevance
“…However, there was highly statistically significant difference regarding backward digit span and letter fluency. These results are concordant with Kwon et al's [45] results which showed insignificance in forward digit span, verbal word recognition, and animals' fluency regarding education. However, their study stated that the performance of the illiterate subjects was worse than that of literate subjects in visuospatial functions and verbal learning test.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, there was highly statistically significant difference regarding backward digit span and letter fluency. These results are concordant with Kwon et al's [45] results which showed insignificance in forward digit span, verbal word recognition, and animals' fluency regarding education. However, their study stated that the performance of the illiterate subjects was worse than that of literate subjects in visuospatial functions and verbal learning test.…”
Section: Discussionsupporting
confidence: 91%
“…The difference between their study and the current study in visuospatial functions could be attributed to the more complexity of Rey-Osterrrieth figure used in their study in comparison to the simple Bender copy in the current study and to the more time delay (20 min) in comparison to 10 min in the current study. Kwon et al 2015 [45] applied the Seoul Verbal Learning Test (SVLT) which is formed of three learning-free recall trials of 12 words which is more difficult than the paired associate of Wechsler applied in the current study which compresses three learning associate recall trials of 10 words.…”
Section: Discussionmentioning
confidence: 98%
“…, 정 상 집단과 비교했을 때 알츠하이머형 치매와 혈관 치매 모두 초기 단계에서부터 두드러지게 저하된다는 등 (Fahlander, Wahlin, Alm kvist, & Bäckman, 2002;Hart & Best, 2014;Henry, MacLeod, Phil lips, & Crawford, 2004;Jones, Laukka, & Bäckman, 2006;Pakho mov & Hemmy, 2014;Park et al, 2006) 다양한 주제로 활발하게 연구가 수행되었으나 의미 유창성만을 다룬 연구들은 상대적으로 많지 않다 (Bolla, Lindgren, Bonaccorsy, & Bleecker, 1990;Capitani, Laiacona, & Basso, 1998;Loonstra, Tarlow, & Sellers, 2001;Phil lips, 1999;RodriguezAranda & Martinussen, 2006 (Kosmidis, Tsapkini, Folia, Vlahou, & Kiosseoglou, 2004 Silva, Petersson, Faisca, Ingvar, & Reis, 2004;Kwon, Cho, Seo, & Na, 2012;Youn et al, 2011), 문해 집단을 교육년 수에 따라서 더 세분화한 연구들도 2개(저학력과 고학력) 정도의 소수의 집단으로만 나누어 비교함으로써 교육수준이 의미 유창성 에 미치는 효과를 자세히 확인하지 못하였다 (Ardila, OstroskySo lis, Rosselli, & Gómez, 2000;Sa et al, 2011 Silva et al, 2004;Kwon et al, 2012;Nielsen & Walde mar, 2016) 그와는 반대로 동물 범주에 있어 문해 집단과 비문해 집 단 간의 수행차이가 유의하지 않다는 연구 결과도 있었다 (Youn et al, 2011). 그러나 또 다른 연구에서는 동물과 가게물건 범주 모두에 서 문해 집단과 비문해 집단 간의 수행차이가 관찰되지 않았다 (Kwon, Yoon, & Na, 2015 (Kang, Chin, Na, Lee, & Park, 2000)가 있고, 그와는 반대로 여성이 남성보다 동물 범주에서 더 많은 반응 수를 보였다는 연구도 있으며 (Weiss, Kemmler, Deisenhammer, Fleis chhacker, & Delazer, 2003), 의미 유창성에 있어 성차를 발견하지 못한 연구들도 있었다 (Choi, 2012a;Mathuranath et al, 2003;Weiss et al, 2006).…”
unclassified